Clinical characteristics of pancreatic cancer presenting with acute pancreatitis: a propensity-matched cohort study - Shi, Jiaqi; Nie, Shuang; Shi, Zhao; Liu, Kun; Zhou, Quan; Wang, Xuan; Jiang, Yihang; Zhang, Song; Peng, Chunyan; Lv, Ying; Tang, Bei; Cheng, Hao; et al. (Surgical endoscopy and other interventional techniques, 2025)
Background and aim: The symptoms of pancreatic cancer (PC) are usually nonspecific or absent, and the early diagnosis remains challenging. 7–14% of PC patients present initially with acute pancreatitis (AP). This study aims to distinguish the PC patients initially presenting with AP from simple AP patients, further evaluating the role of endoscopic ultrasound (EUS) in the early diagnosis. Methods: We retrospectively evaluated 1376 consecutive patients with AP between 2010 and 2023.To overcome selection bias, we used propensity score matching between PC patients initially presenting with AP and non-cancer-related AP patients. Clinical information, especially EUS were collected for comparison. Results: After matching, 72 patients (PC group) and 216 patients (AP group) were included. The unknown etiology in the PC group was significantly higher than that in the AP group (54.2% vs. 27.8%). Regarding initial symptoms, non-cancer-related AP patients exhibited significantly more abdominal distension, vomiting and fever compared to the PC group (p < 0.05). In terms of lab results, PC group patients had lower serum amylase (p < 0.001), but higher CA19-9, CA72-4, and CA242 levels when compared to AP group patients (p < 0.001). Additionally, AP group patients had more systematic and local complications, and the severity of AP was much higher than that of PC group patients. Moreover, PC patients exhibited more frequent imaging findings, such as pancreatic duct dilation or atrophy, and enlarged lymph nodes (p < 0.05). Notably, the EUS examination in PC patients missing diagnosis initially and PC patients presenting with relapsed AP showed more sensitive results and more detective rates. Conclusion: Pancreatic cancer patients presenting initially with acute pancreatitis tend to exhibit mild, recurrent pancreatitis than common AP patients. EUS holds potential diagnostic value in detecting pancreatic cancer in patients with initially negative cross-sectional imaging and recurrent pancreatitis.
Veröffentlicht: 15. April 2025
Gesehen am 01.10.2025